Dam body weight and birth weight in Holstein-Friesians - Negash, Melaku (The Indian Journal of Animal Sciences, 2012)
Records (189) of dam body weight and birth weight each were studied. The 2 measures averaged 506±2.0 and 40.1±0.3 kg, respectively. These are 90 and 82% of the US standard for the same cattle breed. Analyses of variance, where calving year and season and parity were in the model failed to show significant variation of any of the 2 measures due to any of the tested factors. Heritabilities of the 2 traits were also estimated; and they valued 0.35±0.35 and 0.21±0.33 respectively.